Emerging trends in clinical implications of bio-conjugated silver nanoparticles in drug delivery - Prasher, Parteek; Sharma, Mousmee; Mudila, Harish; Gupta, Gaurav; Sharma, Abhishek Kumar; Kumar, Deepak; Bakshi, Hamid A.; Negi, Poonam; Kapoor, Deepak N.; Chellappan, Dinesh Kumar; Tambuwala, Murtaza M.; Dua, Kamal (Colloid and interface science communications, 2020)
From nanopharmaceutics to renewable energy, silver nanoparticles (AgNPs) present innumerable applications in the contemporary era. However, the associated toxicity to the biosystems limits their application. Effective utilization of AgNPs, therefore, requires their surface conjugation with biologically benevolent moieties that enhance the bio-acceptability of silver-based nanosystems, and supplementary functionalities for further extension of their unique applications. The clinical importance of AgNPs was established long ago, but their clinical utilization has been explored only recently with the phenomenon of bio-conjugation. The biomolecule-conjugated AgNPs present operable solutions for tedious clinical complications of the present era, such as multidrug resistance, designing of pharmaceuticals with improved bioavailability, superior drug delivery vehicles and in situ bio imaging of important metabolites that utilize the biomolecule-anchored surface engineered AgNPs. This review epigrammatically discusses some interesting clinical applications of surface conjugated AgNPs with biomolecules such as peptides, nucleic acids, amino acids and antibodies in the current nanopharmaceutical paradigm. [Display omitted] •This review article highlights:•Surface functionalization of AgNPs prior to bioconjugation.•Bio-conjugation strategies for AgNPs.•Various clinical applications of bio-conjugated AgNPs.